2015
DOI: 10.4015/s1016237215500416
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of an Electromagnetic and Optical System During Dynamic Motion

Abstract: Few studies have concurrently investigated the accuracy and repeatability of an optical and electromagnetic (EM) system during dynamic motion. The purposes of this study were to: (1) assess the accuracy of both an EM and optical system when compared to a gold standard and (2) to compare the intra- and inter-day repeatability during 3D kinematic motion of both systems. The gold standard used for accuracy assessment was a robot programmed to manipulate a carbon fiber beam through pre-defined motions within the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Accuracy in EM systems is dependent on the distance between transmitter and receivers, number of receivers in use, and ferromagnetic interference in the capture volume. Similar studies comparing the accuracy of EM and OMC systems have been conducted utilizing markers/receivers applied to a robotic, articulated arm where the true range of motion was known (Hassan et al 2007 ; Lugade et al 2015 ). Hassan et al ( 2007 ) concluded that accuracy of EM and OMC systems were comparable for measuring simulated upper extremity kinematics when appropriate post-hoc filtering and corrections were applied.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Accuracy in EM systems is dependent on the distance between transmitter and receivers, number of receivers in use, and ferromagnetic interference in the capture volume. Similar studies comparing the accuracy of EM and OMC systems have been conducted utilizing markers/receivers applied to a robotic, articulated arm where the true range of motion was known (Hassan et al 2007 ; Lugade et al 2015 ). Hassan et al ( 2007 ) concluded that accuracy of EM and OMC systems were comparable for measuring simulated upper extremity kinematics when appropriate post-hoc filtering and corrections were applied.…”
Section: Discussionmentioning
confidence: 90%
“…The authors did not assess repeatability of the tracking systems using an in vivo model. Lugade et al ( 2015 ) reported sagittal plane lower limb joint angles during a sit-to-stand activity, finding that OMC had lower RMS errors and higher intra- and inter-day CMC values (0.99 ± 0.001; 0.97 ± .025) than EM (0.97 ± 0.05; 0.94 ± 0.038) but concluded that both systems were adequate for tracking dynamic motion (Lugade et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have placed sensors at known distances to the transmitter or to each other, often using assessment phantoms such as grid boards [1-4, 6, 8, 35]. Other studies have characterized the accuracy of EM systems by comparing EM measurements to a standard, such as a robot [36] or materials testing device [8], optoelectronic motion capture system [5,36,37], inclinometer [15], pendulum potentiometer [38], inertial-ultrasound hybrid motion capture system [39], or linkage digitizer [7].…”
Section: Additional Methodological Considerationsmentioning
confidence: 99%
“…Even though the measurement accuracy of the magnetic sensors has been assessed by bone pin data (Karduna et al, 2001), it is noted that the skin movement may be limited by the bone pins (Ramsey et al, 2003;Cappozzo et al, 2005). Electromagnetic tracking devices are also susceptible to nearby metal interference (Lugade et al, 2015). IMUs have been assessed for accuracy by using an optoelectronic system during functional tasks, giving RMS errors of less than 3.6 • (Cutti et al, 2008), which may be attributed to the so-called inertial sensor drift (Luinge et al, 2007) and linear acceleration interference (Zhang et al, 2012) apart from skin movement artifacts.…”
Section: Introductionmentioning
confidence: 99%